Ethnobotany, conservation and sustainable development (1996)
The current attempt to concentrate on medicinal plants as sources of drug is a welcome development which must be accompanied with adequate conservation strategies through research, education and training, ex-situ and in-situ conservation. Conservation is necessary if the dignity of life is to be maintained. However, plant taxonomy as a discipline particularly the aspect of floristic taxonomy, should serve as the ‘bedrock’ of any conservation strategy. Data from such studies which are well documented in efficient and well equipped herbaria in an easily retrievable manner will facilitate better coordinated effort at mapping out strategies for bio conservation and sustainable living. The setting up of Botanical and Zoological gardens is also crucial to conservation programmes. Taxonomists, conservation experts and policy makers must work in harmony and at more organised setting to provide solutions to conservation problems.